2008
DOI: 10.1063/1.2913242
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between bonding and magnetism in the binding of NO to Rh clusters

Abstract: We have studied the adsorption of NO on small Rh clusters, containing one to five atoms, using density functional theory in both spin-polarized and non-spin-polarized forms. We find that NO bonds more strongly to Rh clusters than it does to Rh(100) or Rh(111); however, it also quenches the magnetism of the clusters. This (local) effect results in reducing the magnitude of the adsorption energy, and also washes out the clear size-dependent trend observed in the non-magnetic case. Our results illustrate the comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 58 publications
(84 reference statements)
5
36
1
Order By: Relevance
“…Out of the six Rh atoms present in the unit cell, the spin polarization of each of the two Rh atoms to which N is attached is negligible, while the spin polarization of those atoms to which O is attached is reduced by about 81% and the spin polarization of the two Rh atoms which are furthest from the NO is reduced by about 28%. Similar effects have also been observed previously by us for NO adsorbed on small Rh clusters 33 and by Hass et al 34 in their studies of NO adsorption on a hypothetical monolayer of Rh atoms. Apart from the fact that the latter group of authors worked with a monolayer of Rh ͑i.e., there was no substrate͒, there are other differences between our calculations and theirs: they did the calculations for NO adsorbing in the VB geometry alone, fixed the Rh-Rh distance at the value for bulk Rh, and did not relax the coordinates of NO.…”
Section: E Case (Iv)-monolayer Of Rh On Mgo(100) At Mgo Lattice Conssupporting
confidence: 89%
“…Out of the six Rh atoms present in the unit cell, the spin polarization of each of the two Rh atoms to which N is attached is negligible, while the spin polarization of those atoms to which O is attached is reduced by about 81% and the spin polarization of the two Rh atoms which are furthest from the NO is reduced by about 28%. Similar effects have also been observed previously by us for NO adsorbed on small Rh clusters 33 and by Hass et al 34 in their studies of NO adsorption on a hypothetical monolayer of Rh atoms. Apart from the fact that the latter group of authors worked with a monolayer of Rh ͑i.e., there was no substrate͒, there are other differences between our calculations and theirs: they did the calculations for NO adsorbing in the VB geometry alone, fixed the Rh-Rh distance at the value for bulk Rh, and did not relax the coordinates of NO.…”
Section: E Case (Iv)-monolayer Of Rh On Mgo(100) At Mgo Lattice Conssupporting
confidence: 89%
“…Clusters of rhodium have been the subjects of continuing experimental and theoretical investigations due to interest in the catalytic properties of the metal. For example, Ghosh and coworkers [1] suggested that Rh clusters are good catalysts for NO reduction. Furthermore, the high activity of rhodium clusters and surfaces for the adsorption and decomposition of N 2 O, CO had been investigated by far-infrared multiple photon dissociation experiments and DFT calculations [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Here I will only mention the most important aspects keeping in mind that magnetism is our primary focus. For Rh 5 , GGA and B3LYP calculations find the sextet and octet spin states in the square pyramid structure to be very close in energy [61,63,64,69,76]. The energy difference is only a few tens of meV.…”
Section: Smaller Rhodium Clustersmentioning
confidence: 87%
“…But Bae et al [63] found the ground state to be a bent rhombus, with the angle of bent nearly 90 0 , in a septet state. Ghosh et al [76] also found the ground state to be a septet but a tetrahedron. These authors also found a quintet square, and a singlet tetrahedron.…”
Section: Smaller Rhodium Clustersmentioning
confidence: 94%